Biostimulants derived from organic urban wastes and biomasses: An innovative approach - Giordana, Alessia; Malandrino, Mery; Zambon, Alfonso; Lusvardi, Gigliola; Operti, Lorenza; Cerrato, Giuseppina (Frontiers in Chemistry, 2023)
We used humic and fulvic acids extracted from digestate to formulate nanohybrids with potential applications in agronomy. In order to obtain a synergic co-release of plant-beneficial agents, we functionalized with humic substances two inorganic matrixes: hydroxyapatite (Ca₁₀(PO₄)₆(OH)₂, HP) and silica (SiO₂) nanoparticles (NPs). The former is a potential controlled-release fertilizer of P, and the latter has a beneficial effect on soil and plants. SiO2 NPs are obtained from rice husks by a reproducible and fast procedure, but their ability to absorb humic substances is very limited. HP NPs coated with fulvic acid are instead a very promising candidate, based on desorption and dilution studies. The different dissolutions observed for HP NPs coated with fulvic and humic acids could be related to the different interaction mechanisms, as suggested by the FT-IR study.